Role of English Language for Business Activities at the Present Era of Global Marketing - Chhetri, Deependra Jaisi (Medha: A Multidisciplinary Journal, 2023)
In this era of globalization, English is an essential language for global business and marketing. When we discuss "globalization," either explicitly or implicitly, the English language is brought up. People all across the world use English for reading, writing, and speaking. An estimated 2 billion people speak English, which is recognized as an official language in several nations. English is a subject that many schools and organizations around the world require pupils to take. Additionally, it is a key topic in college-level courses. Communication in trade, education, and business is frequently conducted in English. It is referred to as the lingua franca or the universal tongue. To participate in the international job and research markets, one must be able to speak and write English. The majority of significant books and films are written and produced in English as their primary language. As a result, we learn more about the English language and appreciate it more. The results of this study demonstrate that during the time of British colonial rule, the English language has played a key role in education and economic operations all over the world. In order to travel or study abroad in the modern world, English proficiency is a requirement. With the information and communication procedures that individuals utilize to interact in this era of globalization, writing competence in English is crucial. As a result, the goal of this essay is to highlight the significance of writing in proper English and several reasons why mistakes can be made while writing business communication documents. Also, this is a qualitative study, and the technique of data collection involved some writing assignments, followed by interviews with some bachelor level students of Baglung. Writing faults in the students' work were discovered by an essay exam. The flaws are analyzed, and the need of learning grammar principles is addressed. A small number of researchers' publications are examined to support this research report. This research is unique in terms of value.